ENTOR Guide: a digital learning tool for electrophiles, nucleophiles and types of organic reactions / Gan Fie Chuen, Noor Fatihah Zulkeply and Asniati Sabil - Chuen, Gan Fie; Zulkeply, Noor Fatihah; Sabil, Asniati (2020)
ENTOR (or Electrophile-Nucleophile & Type of reaction) Guide is a digital learning tool developed by The Enthusiasts from Kolej Matrikulasi Negeri Sembilan (KMNS). ENTOR Guide aims to enhance students’ ability in identifying the electrophiles, nucleophiles and types of organic reactions through non face-to-face (NF2F) activities. It comprises a series of steps linked to notes, videos and formative assessment tests. The content of this innovation is presented in the form of thinking maps which incorporate cognitive learning process with infographics. A study was carried out on 40 KMNS students to review the effectiveness of the ENTOR Guide usage. Pre- and post-tests were used to compare students’ achievement after using ENTOR Guide. The findings showed that ENTOR Guide significantly improved students’ abilities in identifying the electrophiles, nucleophiles and types of organic reactions. There is a significant increase in students’ achievement scores for the post-test (mean score = 8.18) as compared to pre-test (mean score = 4.78). Students also showed positive views towards the usage of the learning tool in ENTOR Guide Questionnaire. ENTOR Guide promotes self-learning among students as it is interactive, user-friendly and easy to access. In addition, ENTOR Guide also enables lecturers to plan and implement NF2F reinforcement activity in a more systematic manner.